2015
DOI: 10.1111/den.12470
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic myointimal hyperplasia of mesenteric veins: Rare case of ischemic colitis mimicking inflammatory bowel disease

Abstract: Idiopathic myointimal hyperplasia of mesenteric veins (IMHMV) is a rare and poorly understood ischemic colitis that occurs in the rectosigmoid colon of predominantly young, previously healthy, male patients. A 76-year-old Japanese man presented to our hospital with a 1-year history of worsening diarrhea, lower abdominal pain, and weight loss (-6 kg). Laboratory evaluation revealed white blood cell count of 13,200/μL, C-reactive protein level of 2.0 mg/dL (normal range, 0.0-0.3), and negative results for stool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Colonic stenoses developed after antibiotic-related cololitis caused by Clostridium difficile progressively, which was confirmed by two barium exams. Sahara K and Kawaratani H reported that it is adult inflammatory bowel disease that causes colonic stenosis, and stool culture suggests Clostridium difficile [ 35 , 36 ], but in our case the underlying disease wasn’t present. This patient did have a history of intestinal infection of Clostridium difficile prior to onset of symptoms though.…”
Section: Discussionmentioning
confidence: 56%
“…Colonic stenoses developed after antibiotic-related cololitis caused by Clostridium difficile progressively, which was confirmed by two barium exams. Sahara K and Kawaratani H reported that it is adult inflammatory bowel disease that causes colonic stenosis, and stool culture suggests Clostridium difficile [ 35 , 36 ], but in our case the underlying disease wasn’t present. This patient did have a history of intestinal infection of Clostridium difficile prior to onset of symptoms though.…”
Section: Discussionmentioning
confidence: 56%
“…Of the 34 cases of IMHMV that occurred in men, usually in late middle age (median age at diagnosis 62 years) . Many of these patients, including our patient, have cardiovascular risk factors or disease . The non‐specific presenting symptoms include diarrhea, usually bloody; lower abdominal pain; and weight loss, resulting in the frequent misdiagnosis of IBD.…”
Section: Discussionmentioning
confidence: 85%
“…The etiology of this nonthrombotic occlusion of mesenteric veins is poorly understood. First described by Genta and Haggitt in 1991, 33 reported cases of IMHMV have now been reported (Table ), and it is likely there are many more misdiagnosed or not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an elastin stain can be used to highlight the elastic laminae present in arteries and absent in the affected veins, an important diagnostic clue [12]. The degree of luminal occlusion is variable but often results in an ischemic pattern of injury such as ulceration, superficial withering of crypts, edema, congestion, and, later on in the disease process, hyalinization and fibrosis of the lamina propria and/or submucosa [3, 6, 11, 17]. Notably absent on histology are chronic inflammatory changes.…”
Section: Discussionmentioning
confidence: 99%